(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
This research paper delves into the challenges encountered in affirming sustainability in Iraq, particularly in the context of international standards. It examines the unique conditions and hurdles facing various sectors and industries in the country as they strive to align with and adhere to global sustainability norms. The study also explores the impact of these international standards on sustainability practices within the Iraqi context. The research finds that enhancing collaboration between businesses and the government could lead to a more supportive legislative and policy framework for sustainability in Iraq. Relying on international sustainability standards in corporate operations contributes to fostering a positive image of Iraq both locally and globally. The paper recommends supporting joint initiatives between private companies and the government in Iraq to boost sustainable development. This could include forming public-private partnerships, cooperative research and development projects, and shared sustainability objectives. Additionally, it suggests promoting the development of a legislative and policy framework that backs sustainability in Iraq. This can be achieved by involving stakeholders in the policy-making process, ensuring transparency, and regularly updating policies to reflect international best practices